Self-Portrait - NC (NC, 1887)
Vincent moved to Paris in 1886, after hearing from his brother Theo about the new, colourful style of French painting. Wasting no time, he tried it out in several self-portraits. He did this mostly to avoid having to pay for a model. Using rhythmic brushstrokes in striking colours, he portrayed himself here as a fashionably dressed Parisian.
Droits indiques par le Rijksmuseum
Keywords: rijksmuseum; orsay; europeana; oeuvre d'art; musee; Van Gogh